Timing of aortic valve replacement in high-gradient severe aortic stenosis: impact of left ventricular ejection fraction. Issue 5 (16th July 2021) - Koutsoukis, Athanasios; Nahory, Louis; Deguillard, Camille; Juguet, William; Nguyen, Annabelle; Fard, Damien; Folliguet, Thierry; Fiore, Antonio; Bergoend, Eric; Gallet, Romain; Mouillet, Gauthier; Derumeaux, Genevieve; et al.
Abstract: Background: Patients with high-gradient (HG) severe aortic stenosis (AS) and left ventricular (LV) dysfunction are at high risk of death. The optimal timing for aortic valve replacement (AVR) is not defined by guidelines. The objective was to define the optimal timing to perform isolated AVR in patients with HG-AS and severe LV dysfunction. Methods: We retrospectively included 233 consecutive patients admitted for severe HG-AS (aortic valve area <1cm 2 and mean gradient ≥40mmHg). Severe LV dysfunction was defined by LV ejection fraction ≤35% (LVEF). All-cause mortality while waiting for AVR and after the intervention (30 days) was compared in patients with ( n = 28) and without ( n = 205) LVEF ≤35%. Results: Patients with HG-AS and severe LV dysfunction had a higher risk profile than those with LVEF >35%. AVR was performed in 93% (218/233) of patients, 41% by surgery (SAVR) and 53% by transcatheter (TAVR). TAVR was the preferred method to treat HG-AS patients with LVEF ≤35%. All-cause mortality while waiting for AVR was higher in patients with severe LV dysfunction (22% vs. 2.0%, p < 0.001) and occurred within a shorter time (12 [8–26] days vs. 63 [58–152] days, p = 0.010) compared to those with LVEF >35%. All death in HG-AS patients with a severe LV dysfunction occurred within the first month. Postoperative mortality was low (1.3%), irrespective of LVEF. Conclusions: AVR should be performed promptly after Heart Team decision in patients with HG severe AS and LVEF ≤35% because of a very high and premature risk of death while waiting for intervention.